Edible Part Nutritional Value And Calcium Content In Five Lai-Durian (D.zibethinus X D. Kutejensis) Fruit Rind From Loa Kulu East Kalimantan - Kurniadinata, Odit Ferry; Wenpei, Song; Saragih, Bernatal; Rusdiansyah, Rusdiansyah (Journal of Tropical Horticulture, 2021)
The large number of Durio species that grow in Kalimantan illustrates that this area is the most important distribution center for durian relatives. Two of the best-known edible durians in East Kalimantan are Durian (Durio zibethinus) and Lai (Durio Kutejensis). Several studies have been conducted to determine the effect of calcium on the quality of fruits. However, very little information was obtained regarding the effect of Ca on the quality of lai-durian fruit. This research was carried out by collecting data and information about Fruit performance and edible part nutritional value three D. zibenthinus x D. kutejensis plants. The five potential superior plants have some similar in rind moisture factor, ash content, water content, total fat, crude protein, and total dissolved solids. However, there is a difference in flesh thickness which indicates that LK4 has the thickest flesh thickness with an average of 9mm, while LK5 shows the thinnest average flesh thickness of 4mm. Meanwhile, when viewed from total carbohydrates, LK3 fruit has the highest total carbohydrate content compared to other fruits, which is 37.477 and energy is 180.357 kcal. This study indicates that there is a negative correlation between fruit peel size and calcium content. In large Lai-durian fruits such as LK4 fruit there is a lower amount of calcium than other fruits.